Software engineering, intelligent systems and visual technology - Goh, Wooi Boon (2008)
The objectives of the RGM-5/95 was to provide funding for the training of graduate students (M.A.Sc., M. Eng and Ph.D.) and research assistant in the area of software Engineering, intelligent systems and visual technology.